KOMBINASI NANOPARTIKEL KITOSAN DAN MODIFIED TAPIOCA-WHEY PROTEIN DALAM PEMBUATAN EDIBLE COATING TERHADAP AKTIVITAS ANTIBAKTERI DAN ORGANOLEPTIK OTAK-OTAK TENGGIRI - Farras Rana Hafizhah; A. Shofy Mubarak; Gunanti Mahasri (Airlangga University, 2024)
Product otak-otak ikan tenggiri is a promising fishery diversification product but is prone to spoilage. Edible coatings can help slow down spoilage. The purpose of this study was to determine the effect of different edible coating formulations on the characteristics of edible coating and to determine the protective potential of edible coatings against bacterial growth and organoleptic product otak-otak ikan tenggiri during storage. This research is an experimental study that is divided into two stages, the first stage is the characteristics of edible coatings using a completely randomized design (CRD) with testing including antimicrobial activity, water absorption, and viscosity with 5 treatments and 4 replicates, and the second stage is coating applications on the length of storage of product otak-otak ikan tenggiri testing including TPC and organoleptic using two-factor CRD 3×6 treatments and 3 replicates. Results indicated a significant impact (P < 0.05) of coating formulations on these characteristics. The best formulation, modified tapioca-WPI with CSNP (P4), showed antibacterial activity with a 9.16 mm inhibition zone, 3.46% water absorption, and 15.33 cP viscosity. This formulation maintained microbial stability and organoleptic quality for up to 3 days at room temperature and 12 days under cold temperature.